MOG antibody disease: A review of MOG antibody seropositive neuromyelitis optica spectrum disorder - Narayan, Ram; Simpson, Alexandra; Fritsche, Katelyn; Salama, Sara; Pardo, Santiago; Mealy, Maureen; Paul, Friedemann; Levy, Michael (Multiple sclerosis and related disorders, 2018)
•MOG antibody disease is the most recent antigen specific autoimmune disease on the NMO Spectrum.•MOG antibody disease is characterized by optic neuritis and less commonly transverse myelitis with generally better outcomes compared to the AQP4 NMO.•Half of MOG antibody positive cases remain monophasic after the initial attack. MOG antibody disease is an autoimmune disease of the central nervous system associated with a serological antibody against MOG, myelin oligodendrocyte glycoprotein. MOG is a glycoprotein expressed on the outer membrane of myelin and solely found within the central nervous system, including in the brain, optic nerves and spinal cord. Clinically, the disease resembles neuromyelitis optica spectrum disorders in the predilection for relapses of optic neuritis and transverse myelitis. In addition, acute disseminated encephalomyelitis (ADEM) is a well-recognized phenotype of MOG antibody disease in children. In recent studies around the world where MOG testing is available, up to 42% of NMOSD patients who test seronegative for the AQP4 antibody test positive for MOG antibodies. MOG antibody disease has thus recently emerged as a distinct entity carved out of the patient population diagnosed with NMOSD. In this review, we examine the history of the MOG antibody and its relevance to demyelinating disease, as well as compare the clinical, radiographic and serological profiles of patients with MOG antibody with patients with AQP4 antibody.